1999
DOI: 10.1146/annurev.phyto.37.1.369
|View full text |Cite
|
Sign up to set email alerts
|

NATURAL GENOMIC AND ANTIGENIC VARIATION IN WHITEFLY-TRANSMITTED GEMINIVIRUSES (BEGOMOVIRUSES)

Abstract: Begomoviruses have circular single-stranded DNA genomes, cause many diseases of dicotyledons in areas with warm climates and are transmitted by whiteflies of the Bemisia tabaci complex. Their genomic and antigenic variation represents geography-related lineages that have little relation to host range. Genomic variation resulting from mutation is amplified by acquisition of extra DNA components, pseudo-recombination and recombination, both intraspecific and interspecific. Recombination, especially interspecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(121 citation statements)
references
References 93 publications
3
117
0
1
Order By: Relevance
“…[16,77,86,116]. Recombination has played a major role in evolution and emergence of new one among species/strains [58]. Earlier it was believed that DNA viruses are less prone to recombination but certain studies found that begomoviruses are highly prone to recombination [49,82,105,149].…”
Section: Molecular Based Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…[16,77,86,116]. Recombination has played a major role in evolution and emergence of new one among species/strains [58]. Earlier it was believed that DNA viruses are less prone to recombination but certain studies found that begomoviruses are highly prone to recombination [49,82,105,149].…”
Section: Molecular Based Approachesmentioning
confidence: 99%
“…This recombination leads to the formation of virulent strain than parent virus [149] and RNAi suppression of plant defence by begomoviruses is the key factor responsible for the disease development and transmission of virus [155]. In the early 1990s, geminiviruses caused up to 95% yield losses of tomatoes in the Dominican Republic, and inflicted over US$2 billion/year yield losses in cassava in Africa [58]. In Brazil, during the last four years, more than 11,000 jobs have been lost in the tomato industry because of whitefly-transmitted geminiviruses and other factors.…”
Section: Molecular Based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both, immune-and nucleo-based techniques have been employed for the detection of begomoviruses [5]. Begomoviruses are phloem limiting, generally not sap transmissible and many of them do not have suitable propagative hosts.…”
mentioning
confidence: 99%
“…To identify the optimum dilution of infected leaf sap, two fold dilutions of the infected leaf extracts [1:2, 1:4, 1:8, 1:16, 1:32, 1:64, 1:128 and 1:256] were evaluated by ELISA. In order to determine the minimum quantity of viral antigen required for ELISA detection, purified recombinant CP at different concentrations [5,10,25, 50, 100, 500 and 1,000 ng] were tested. The antiserum showed titer of 1:250, when tested repeatedly with infected crude extract as antigen.…”
mentioning
confidence: 99%